Orthorexia nervosa in gay men-the result of a spanish-polish eating disorders study - Piotr Karniej; Jesús Pérez; Raúl Juárez-Vela; Iván Santolalla-Arnedo; Vicente Gea-Caballero; Pablo del Pozo-Herce; Anthony Dissen; Michał Czapla (BMC, 2023)
Abstract Background The purpose of this exploratory study was to identifying demographic factors and unique predictors of ON e.g., the use of pre-exposure prophylaxis (PrEP), the use of social media and the Grindr ® dating application among a sample group of Spanish and Polish identifying gay men. Methods The study was conducted in Poland and Spain between March and June 2021 using questionary: ORTO-15. Data was collected using a three-section self-administered questionnaire. The first section contained demographic data, the second part was the Polish and Spanish version of the Orto-15, and the third part was the Polish and Spanish version of the EAT-26. Results Total enrollment was 394 gay men. In regression proportional hazards single model, significant predictors of ON were: age (OR = 0.964, 95% CI, 0.944-0.984), BMI (OR = 0.895, 95% CI, 0.848-0.944), staying in an informal relationship compared to being single (OR = 2.138, 95%CI, 1.225-3.732), occasional use of Pre-exposure Prophylaxis (OR = 4.667, 95%CI, 1.186-18.362) and use of the Grindr application (OR = 5.312, 95%CI, 3.373-8.365). Instagram users had lower risk of ON (OR = 0.479, 95%CI, 0.279-0.822). The multivariate analysis showed that Grindr usages (OR = 4.72; 95%CI, 2.89-7.72) correlated with higher risk of ON. Higher BMI (OR = 0.913, 95%CI, 0.861-0.98) and daily use of Pre-exposure Prophylaxis (OR = 0.142, 95%CI, 0.03-0.674) is associated with lower risk of ON. Conclusions The most important predictors of orthorexia nervosa in gay men are: low BMI and the use of Grindr. The effect of daily usage of PrEP is associated with lower risk, and occasional use is associated with increased risk, of orthorexia nervosa.